2015
DOI: 10.1186/2044-7248-4-12
|View full text |Cite
|
Sign up to set email alerts
|

Temporal design of taste and flavor: practical collaboration between chef and scientist

Abstract: Background: Recently, many chefs have collaborated with researchers and used scientific techniques in their cooking. These researchers advise chefs from a scientific perspective. However, they do not know what chefs think and what concept they want to express through their dishes. Once scientists understand what motivates chefs in the creation of their new dishes, they would be able to provide chefs with more precise advice. Findings: The authors identified culinary success factors (CSFs) from context analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Such records may see a revival in the coming years as Western countries seek a renewal of seaweed in their diet. Modern takes on traditional ingredients is a popular trend in the culinary industry, as was seen in a collaboration between Michelin-starred chef Koji Shimomura and scientist Hiroya Kawasaki who designed a new seaweed dish based on nutritional value and taste [169]. Rioux (2017) reviewed seaweeds as an ingredient to be utilized by the food industry as a traditional ingredient for a "new gastronomic sensation", recognizing its potential to deliver valuable bioactive nutrients to the consumer, as well as using seaweed as "a vector of flavour and texture" [170].…”
Section: Seaweed Gastronomymentioning
confidence: 99%
“…Such records may see a revival in the coming years as Western countries seek a renewal of seaweed in their diet. Modern takes on traditional ingredients is a popular trend in the culinary industry, as was seen in a collaboration between Michelin-starred chef Koji Shimomura and scientist Hiroya Kawasaki who designed a new seaweed dish based on nutritional value and taste [169]. Rioux (2017) reviewed seaweeds as an ingredient to be utilized by the food industry as a traditional ingredient for a "new gastronomic sensation", recognizing its potential to deliver valuable bioactive nutrients to the consumer, as well as using seaweed as "a vector of flavour and texture" [170].…”
Section: Seaweed Gastronomymentioning
confidence: 99%
“…Also, important attributes of food, on which the choice by the guests depends, can be classified into six categories: 1) energy content, 2) nutrient content/health properties, 3) taste, 4) prestige status/properties, 5) ecological, political and ethical characteristics and 6) attributes of time/convenience (Jang et al, 2009). The success of new dishes depends on several factors identified and analyzed by some authors (Kawasaki & Shimomura, 2015;Klosse et al, 2004). Based on the interviews with 18 chefs and analysis of 63 dishes, six critical success factors (CSFs) were identified by Klosse et al (2004).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Namely, the success of new dishes depends on several factors. Previous studies (Kawasaki & Shimomura, 2015;Klosse et al, 2004) examined CSFs in the Netherlands and Japan, however, thus far, this topic has not been researched in Serbia and the southeastern region of Europe. In addition, previous studies did not analyze the hierarchy of identified CSFs, therefore, their importance for the success of new dishes which are part of the gastronomic offer is not known.…”
Section: Introductionmentioning
confidence: 99%
“…The papers deal with the following topics: the comparative biology of taste [9]; fat as a basic taste [10]; umami taste in relation to gastronomy [11]; the mechanism of kokumi taste [12]; geography as a starting point for deliciousness [13], temporal design of taste and flavor [14]; the pleasure principle of flavors [15]; taste as a cultural activity [16]; taste preferences in primary school children [17]; taste and appetite [18]; umami taste in relation to health [19]; taste receptors in the gastrointestinal tract [20]; neuroenology and the taste of wine [21]; the brain mechanisms behind pleasure [22]; the importance of sound for taste [23]; as well the effect of kokumi substances on the flavor of particular food items [24,25].…”
mentioning
confidence: 99%